Implementation of The Prosecutor's Intelligence Authority in Investigations of Corruption Crimes - Tuanaya, Nurjanah; Malik, Faissal; Amriyanto (Lembaga Penelitian dan Pengabdian Masyarakat, 2024)
This study aims to analyze the implementation of the Prosecutorial Intelligence's authority in investigating alleged corruption at the Tidore Kepulauan District Attorney's Office and to identify the challenges encountered during the investigation process. The methodology employed is empirical legal research with a qualitative field approach. Data were collected through in-depth interviews and documentation studies. The research findings indicate that the implementation of the Prosecutorial Intelligence's authority at the Tidore Kepulauan District Attorney's Office aligns with the applicable regulations, including Article 30B paragraph (d) of Law No. 11 of 2021 on the Amendment of Law No. 16 of 2004 on the Prosecutor's Office of the Republic of Indonesia and Presidential Regulation No. 38 of 2010 on the Organization and Working Procedures of the Prosecutor's Office of the Republic of Indonesia. Nonetheless, several significant challenges were identified in the investigation process, including budget constraints, insufficient education and training for staff, and inadequate facilities and infrastructure. This study provides recommendations to address these challenges, including increasing budget allocations, conducting regular training for Prosecutorial Intelligence staff, and providing adequate supporting facilities to enhance the effectiveness of corruption investigations.